Relationship between albumin-corrected anion gap and non-alcoholic fatty liver disease: a cross-sectional analysis of NHANES 2017–2018 - Bai, Ning; Ying, Ting; Li, Dejian; Liu, Aiguo (Frontiers in Medicine, 2025)
ObjectivesThe objective of this study was to examine the correlation between the albumin-corrected anion gap (ACAG) and non-alcoholic fatty liver disease (NAFLD) using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018.MethodsA cross-sectional analysis was conducted, comprising 4,379 participants, who were stratified into two groups: those with NAFLD and those without NAFLD. The baseline characteristics were compared using the most appropriate statistical tests. The relationship between ACAG levels and NAFLD was assessed using generalized linear models, with adjustments made for potential confounding factors. The analysis of threshold effects was conducted using piecewise regression. Furthermore, the relationship between ACAG and NAFLD was investigated in different age groups.ResultsThe mean age of participants with non-alcoholic fatty liver disease (NAFLD) was significantly higher than that of non-NAFLD participants (48.88 vs. 43.46 years, p < 0.001). The presence of NAFLD was associated with higher levels of ACAG (18.80 ± 0.24 vs. 18.10 ± 0.19, p < 0.001). In fully adjusted models, each 1-unit increase in ACAG was associated with a significantly increased risk of NAFLD in participants under 60 years old (β: 0.87, 95% CI: 0.05, 1.69, p < 0.05). In younger participants, elevated NAFLD risk was observed in those with higher ACAG quartiles (P for trend <0.05). In contrast, no significant associations were identified in participants aged 60 years and older (P for trend >0.05), suggesting the presence of age-specific differences in the relationship between ACAG and NAFLD.ConclusionThe impact of ACAG on NAFLD is significantly correlated, especially in the age group, where elevated levels of ACAG are associated with increased risk of NAFLD in young people. ACAG may be a potential and reliable biomarker for predicting NAFLD risk in clinical assessment, but its implementation should consider the patient’s age factor.